EFEKTIVITAS KEGIATAN EKSTRAKURIKULER TILAWAH DALAM MENINGKATKAN SENI BACA AL-QUR’AN SANTRI DI PONDOK TAHFIDZ QURAN NURUL ASYKAR - Ahmad; Wahab, Abdul; Bunyamin, Andi; Nengsih, Ratika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to describe the implementation of extracurricular activities of Al-Qur'an recitation and analyze its effectiveness in improving the quality of the art of reading the Al-Qur'an of students at the Nurul Asykar Qur'an Tahfidz Boarding School in Sidrap Regency. This study uses a descriptive qualitative research type with a case study approach. The research subjects consisted of tahfidz instructors, extracurricular recitation instructors, and 44 students who participated in extracurricular recitation activities. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using an interactive analysis model that includes data collection, data reduction, data presentation, and drawing conclusions, while the validity of the data was tested through source triangulation, technical triangulation, and time triangulation. The results of the study indicate that the implementation of extracurricular activities of Al-Qur'an recitation has been running well through systematic planning, the use of lecture methods, demonstrations, talaqqi, and direct practice, and supported by the active role of instructors in guiding, motivating, and evaluating the abilities of students. This activity is also supported by the availability of adequate facilities and infrastructure and high student participation. The effectiveness of the activity is seen from the increasing ability of students in the aspects of tajwid, makharijul huruf, fashahah, mastery of the basics of nagham, etiquette of reading the Qur'an, and self-confidence to appear to read the Qur'an in front of others. However, there are still several obstacles, especially in the aspect of breath regulation and mastery of rhythm variations that require continuous practice. Thus, the extracurricular activity of recitation of the Qur'an at the Nurul Asykar Qur'an Tahfidz Pondok in Sidrap Regency has proven effective in improving the quality of the art of reading the Qur'an of students and becoming a forum for developing the abilities, talents, and mentality of students to perform in accordance with the correct rules of recitation.